An effective adaptive time domain formulation to analyse acoustic–elastodynamic coupled models. (September 2017) - Soares, Delfim; Almeida, Victor B.C.
Highlights: A simple and effective new coupling algorithm is proposed. Each subdomain of the coupled model is analysed independently. Explicit/implicit adaptive time integrators are considered. It provides enhanced accuracy and advanced controllable numerical dissipation. It is a generic, efficient, easy to implement and entirely automatic procedure. Abstract: This work is concerned with the development of an effective technique to model the propagation of interacting acoustic and elastic waves. Here, spatial discretization by finite elements is adopted, and uncoupled analyses of acoustic and elastodynamic subdomains are considered, with the interaction between the different subdomains of the model being accomplished by interface forces. Adaptive explicit and implicit time-marching techniques are employed, in which the time integrators are locally computed, assuming different values along the spatial and temporal discretizations, as the solution evolves. The proposed solution algorithm is very efficient, accurate, flexible and easy to implement, standing as a very attractive approach. At the end of the paper, numerical results are presented, illustrating the good performance and potentialities of the new methodology.